2011
DOI: 10.1111/j.1745-3933.2010.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

The Subaru Lyα blob survey: a sample of 100-kpc Lyα blobs at z = 3

Abstract: We present results of a survey for giant Lyα blobs (LABs) at z= 3 with Subaru/Suprime‐Cam. We obtained Lyα imaging at z= 3.09 ± 0.03 around the SSA22 protocluster and in several blank fields. The total survey area is 2.1 deg2, corresponding to a comoving volume of 1.6 × 106 Mpc3. Using a uniform detection threshold of 1.4 × 10−18 erg s−1 cm−2 arcsec−2 for the Lyα images, we construct a sample of 14 LAB candidates with major‐axis diameters larger than 100 kpc, including five previously known blobs and two known… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
166
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(180 citation statements)
references
References 62 publications
11
166
0
Order By: Relevance
“…The number of known LABs is still not very large. For example, a narrow-band imaging survey with the Subaru/Suprime-Cam revealed 14 LAB candidates with a mayor axis diameter larger than 100 kpc (Matsuda et al 2011). Their shapes range from circular to filamentary.…”
Section: The Cosmic Web In Emissionmentioning
confidence: 99%
“…The number of known LABs is still not very large. For example, a narrow-band imaging survey with the Subaru/Suprime-Cam revealed 14 LAB candidates with a mayor axis diameter larger than 100 kpc (Matsuda et al 2011). Their shapes range from circular to filamentary.…”
Section: The Cosmic Web In Emissionmentioning
confidence: 99%
“…This strong absorption has also been observed using Keck/HIRES , which confirmed that this absorption is consistent with the superposition of the intergalactic Lyα forest rather than LLSs or DLAs. In the upper right panel, we present an absorption system at similar redshift as the galaxy overdensity (z = 3.09), with an effective optical depth on 15 h Giant Lyα nebulae (also known as Lyα blobs, LABs) are characterized by a high luminosity of the Lyα line emission (L (Lyα)10 43 erg s −1 ) and a spatially large Lyα emitting region from tens of kiloparsec (kpc) up to intergalactic scales of hundreds of kpc (e.g., Matsuda et al 2005Matsuda et al , 2011Yang et al 2009Yang et al , 2010Yang et al , 2014. Previous studies suggest that LABs are strongly clustered sources.…”
Section: Ssa22 Protocluster At Z = 31mentioning
confidence: 99%
“…When studied in detail, these systems show complex morphologies, obscured active galactic nuclei (AGNs), and/or associated star-forming galaxies (e.g., Francis et al 1996;Ivison et al 1998;Steidel et al 2000;Palunas et al 2004;Chapman et al 2004;Matsuda et al 2004Matsuda et al , 2007Basu-Zych & Scharf 2004;Dey et al 2005;Geach et al 2007;Smith et al 2008;Prescott et al 2009;Ouchi et al 2009;Yang et al 2011). There is strong evidence that the largest Lyα nebulae are rare (Saito et al 2006;Yang et al 2009Yang et al , 2010Prescott 2009;Matsuda et al 2011) and typically reside in the most overdense regions of the universe (e.g., Palunas et al 2004;Matsuda et al 2004Matsuda et al , 2005Matsuda et al , 2009Saito et al 2006;Prescott et al 2008;Yang et al 2009). …”
Section: Introductionmentioning
confidence: 99%